Pamięć i rzeczy : O narracjach autobiograficznych Lydii Flem i Marcina Wichy (Politeja, 2020)
Memory and Objects. About the Autobiographical Narratives Written by Lydia Flem and Marcin WichaThe aim of paper is to discover traces of the deceased and recreate bonds between a human and an object (objects). In the narrative two autobiographies were analysed: Lydia Flem’s ‘How I emptied my parents’ house’ (‘Comment j’ai vidé la maison de mes parents’) and Marcin Wicha’s ‘Items I didn’t throw away’ (‘Rzeczy, których nie wyrzuciłem’). Both authors mourn their mothers. According to the specific Jewish ‘idiom’ they run a post-cmemorial thread related to their mothers’ origins and historical implications (post-memory is understood, after Marianne Hirsch, as a specific kind of transfer of some traumatic experience).